Secondary Amenorrhea and Infertility Due to an Inhibin B Producing Granulosa Cell Tumor of the Ovary. A Rare Case Report and Literature Review - Corina Gică; Ruxandra-Gabriela Cigăran; Radu Botezatu; Anca Maria Panaitescu; Brîndușa Cimpoca; Gheorghe Peltecu; Nicolae Gică (Medicina, 2021)
Granulosa cell tumor of the ovary (GCT) is a rare ovarian tumor with nonspecific symptoms. Studies reported that GCT are usually secreting estrogens and inhibins, especially inhibin B. It is considered that, in premenopausal women, irregular menses or secondary amenorrhea may be an early symptom of GCT and, in postmenopausal women, the most common manifestation is vaginal bleeding. Additionally, endometrial abnormalities can be associated due to estrogenic secretion. At reproductive age, high levels of inhibin, lead to low levels of FSH and secondary amenorrhea causing infertility. At times, increased levels of LH in women with GCT are observed and the pathogenesis is still unclear. Therefore, inhibin B level can differentiate GCT from other causes of secondary amenorrhea. We report the case of a 26-year-old nulliparous, women who presented in our clinic with secondary infertility lasting longer than 2 years, secondary amenorrhea, polycystic ovarian syndrome, and suspicion of right ovarian endometrioma on CT scan. The ultrasound examination revealed that the right ovary was transformed in an anechoic mass with increased peripheral vascularity having a volume of 10 cm3. This patient had high serum levels of inhibin B and LH but normal levels of FSH and estradiol. The preliminary diagnosis of granulosa cell tumor of the ovary was made. After counseling, the informed consent for treatment was obtained and the patient agreed to undergo surgery. An uneventful laparoscopy was performed with right oophorectomy and multiple peritoneal sampling. The histological diagnosis confirmed adult GCT limited to right ovary, with negative peritoneal biopsies (FIGO IA). After surgery the patient recovered fully and had normal menstrual cycles with normal serum levels of hormones. Two months later she conceived spontaneously and had an uneventful pregnancy. In conclusion, for cases with secondary amenorrhea, the evaluation of inhibin B level is essential. Elevated inhibin B level may be a sign for the presence of an unsuspected tumor. With early diagnosis and treatment, the prognosis is generally good and the fertility may be preserved, especially in young patients with GCT.